Development of a GMO-free de novo lager yeast with reduced phenolic off-flavor production through interspecific hybridization and UV mutagenesis - Chiara Nasuti; Gabriele Iannuzziello; Viola Ceramelli Papiani; Davide Tagliazucchi; Kristoffer Krogerus; Lisa Solieri (International Journal of Food Microbiology, 2026)

Genomic and Proteolytic Profiling of Lacticaseibacillus sp. PRA205: Insights into PepX-Mediated Bioactive Peptide Metabolism - Marianna Cristofolini; Alice Cattivelli; Alessandra Barbieri; Giulia Zaccarini; Loris Bertoldi; Lisa Solieri; Davide Tagliazucchi (Probiotics and Antimicrobial Proteins, 2026)

Bile Salt Hydrolase Activity in the Food-Derived Strain Levilactobacillus brevis M3R3: Genomic and Functional Characterization - Gianluigi Agolino; Marianna Cristofolini; Maria Anna Ronsivalle; Alice Cattivelli; Davide Tagliazucchi; Cinzia Caggia; Lisa Solieri; Cinzia L. Randazzo (Probiotics and Antimicrobial Proteins, 2026)
In the present study, Levilactobacillus brevis M3R3, isolated from traditional Sicilian sourdough, was evaluated for bile salt hydrolase (BSH) activity through kinetic growth assays and bile salts (BSs) deconjugation analysis by UHPLC/HR-MS. Genome sequencing and in silico analyses were performed to assess its safety and probiotic potential. Results showed that strain M3R3 tolerated different concentrations of individual conjugated BSs, with dose-dependent growth inhibition. Exposure to 1.0% glycocholic and glycodeoxycholic acids reduced M3R3 growth, indicating an adaptive stress response. When exposed to a mixed BS solution mimicking intestinal conditions, the strain maintained growth despite an extended lag phase and a reduced final biomass, likely due to toxic BSs accumulation. UHPLC/HR-MS confirmed complete deconjugation of glyco-conjugated BSs and partial deconjugation of tauro-conjugated BSs. Whole-genome sequencing (2.30 Mbp, 2375 CDSs) revealed absence of antimicrobial resistance or virulence genes and identified two bsh genes ( bsh_2A and bsh_3A ), both expressed under control and BS-exposed conditions. Phylogenetic analysis of L. brevis BSH proteins identified three clusters (I, II, and III), with bsh_2A and bsh_3A from M3R3 grouped in clusters II and III, respectively. Overall, genomic and functional characterizations support that L. brevis M3R3 is a safe, BSH-active strain, with potential applications as a functional ingredient in health promoting formulations.

Development of a new prototypal natural whey starter production system to study biodiversity and technological features fluctuations during back-slopping practice used in Parmigiano Reggiano PDO cheese production: penicillin G as a case study - Marianna Cristofolini; Maria Anna Ronsivalle; Davide Manicardi; Valentina Pizzamiglio; Valeria Musi; Elena Bortolazzo; Lisa Solieri (Food Microbiology, 2026)

Peptidomics and biological activity analysis of in vitro digested Parmigiano Reggiano cheese at different ripening stages - Alice Cattivelli; Lisa Solieri; Serena Martini; Valentina Pizzamiglio; Davide Tagliazucchi (International Dairy Journal, 2024)